If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = 2(x + 5) * answer Reorder the terms: 3x = 2(5 + x) * answer Reorder the terms for easier multiplication: 3x = 2aenrsw(5 + x) 3x = (5 * 2aenrsw + x * 2aenrsw) 3x = (10aenrsw + 2aenrswx) Solving 3x = 10aenrsw + 2aenrswx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2aenrswx' to each side of the equation. -2aenrswx + 3x = 10aenrsw + 2aenrswx + -2aenrswx Combine like terms: 2aenrswx + -2aenrswx = 0 -2aenrswx + 3x = 10aenrsw + 0 -2aenrswx + 3x = 10aenrsw Reorder the terms: -10aenrsw + -2aenrswx + 3x = 10aenrsw + -10aenrsw Combine like terms: 10aenrsw + -10aenrsw = 0 -10aenrsw + -2aenrswx + 3x = 0 The solution to this equation could not be determined.
| 35*(x-2)= | | 0=-4x^2+9x+3 | | 0=-2x^2+5x+3 | | 72-(5x+15)=5(x+7)+x | | 0=-3x^2+7x+2 | | -l-19l-l-23-2l= | | 4.3333333x+4=1.5x+3 | | 3p^2=-8p-4 | | 4c^2+21c+27=0 | | 3x-6=2-x | | 3x-6=2-4 | | x-3=2x-2 | | -24+14=m | | -5r-7r+2=5r-r | | 7(x-3)=4x+5 | | z+3(z-1)-2-3(z-1)=0 | | -x^2+8x=-37 | | h(t)=-16t^2+128t+6 | | 4-2x=9x+21 | | 4x-2=32 | | -5x+8=-3+10 | | 2x^2-x+20=0 | | 2x^2+1=49 | | y=10x^2+3x-7 | | 3(ax-4)=2(x-a)-5 | | 2x^2+25=49 | | 3(ax-4)=2(x-a) | | 4x^2+9=6 | | 2=0.15 | | 3(x-2b)-9a-15b=0 | | y-x+1=x+6x^2 | | ln(X+3)+ln(X-1)=0 |